Epistemic Violence and Spiritual Displacement in Postcolonial Nigeria: A Comparative Study of Chinua Achebe’s Things Fall Apart and Chimamanda Ngozi Adichie’s Purple Hibiscus - P.Antony Maria Jenobhar (ILN Journal: Indian Literary Narratives, 2025)
This article investigates the concept of epistemic violence and spiritual dislocation in postcolonial Nigeria through a comparative examination of Chinua Achebe’s Things Fall Apart (1958) and Chimamanda Ngozi Adichie’s Purple Hibiscus (2003). It posits that both novels illustrate how colonialism, in addition to exerting political dominance, systematically undermines indigenous knowledge systems, spiritual practices, and cultural identities. Achebe’s portrayal of the gradual disintegration of Igbo society evidenced by the weakening of the Oracle, the silencing of ancestral voices, and the neglect of rituals, demonstrates how colonial forces invalidate traditional worldviews. In a similar vein, Adichie depicts the enduring repercussions of colonial rule within familial structures, where rigid religious tenets stifle personal freedom and cultural expression. Highlighting the postcolonial theoretical frameworks, particularly Gayatri Spivak’s notion of epistemic violence and Frantz Fanon’s insights on psychological alienation, this study unveils how colonial authority reconfigures reality, truth, and self-identity. The tragic decline of Okonkwo and the internal struggles of Kambili and Jaja serve as representations of the wider cultural crisis and identity loss that accompany epistemic oppression. This paper asserts that epistemic violence transcends historical contexts, remaining a pervasive influence in contemporary families and communities. Through resilience, consciousness, and cultural reclamation, Achebe and Adichie propose avenues for resistance and healing against imposed ideologies.